(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the issue of cultural memory in the poetry of Alexander Faynberg. The study examines the artistic interpretation of historical and cultural images in the poet’s poetics as well as the poetic expression of cultural memory. Poetic symbols related to history, culture, and human memory in Faynberg’s poems are analyzed, and their artistic functions are identified. Based on the theory of cultural memory, the article explores the artistic representation of historical experience and cultural heritage in the poet’s works. The research demonstrates that cultural memory in Faynberg’s poetry functions as an important artistic factor enriching poetic meaning and expanding the semantic layers of the literary text.